Manajemen Sarana dan Prasarana di Sekolah Dasar Inpres Bumi Sagu Kelurahan Besusu Kota Palu - Masuari, Nur Alfiqah; Mufti, Muhammad Irfan; Mayusa, Askar (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2025)
Poorly systematic planning, budget constraints, low human resources, and lack of managerial initiative serve as obstacles in managing facilities and infrastructure. Consequently, this results in poorly maintained, damaged, and unusable facilities and infrastructure. The purpose of this research is to understand how facilities and infrastructure are managed at SD Inpres Bumi Sagu. The research foundation used in this study is a qualitative approach with a descriptive type. The data sources used are primary and secondary data. The informants involved in this research number 5 people, with informant selection using purposive sampling technique. Data collection techniques used include observation, interviews, and documentation. Data analysis steps include data collection, data condensation, data presentation, drawing conclusions, and verification. The research results show that planning for facilities and infrastructure at SD Inpres Bumi Sagu does not yet meet needs, with frequent procurement of goods without going through a mature needs planning process; SD Inpres Bumi Sagu does not yet have a digital-based reporting system; the existing facilities and infrastructure are still suboptimal; and recording and documentation of disposed goods are not well organized. The conclusion is that the management of school facilities and infrastructure has generally met basic educational needs, but there are deficiencies in routine maintenance, such as building damage due to extreme weather in Palu, as well as budget constraints that hinder the procurement of modern technological facilities like computers or projectors. Therefore, improvements in maintenance and innovation are needed to enhance educational quality. Suggestions include improving the maintenance system for facilities and infrastructure, allocating special budgets for early repairs, and collaborating with the local education office to obtain technical assistance or additional funds.